Spectral Assessment of the Effects of Base Flexibility on Seismic Demands of a Structure - J. Borzouie; J. G. Chase; G. A. MacRae; G. W. Rodgers; G. C. Clifton (Advances in Civil Engineering)
Base flexibility of structures changes and can increase the demands on structural elements during earthquake excitation. Such flexibility may come from the base connection, foundation, and soil under the foundation. This research evaluates the effects of column base rotational stiffness on the seismic demand of single storey frames with a range of periods using linear and nonlinear time history analysis. The base rotational stiffness ranges considered are based on previous studies considering foundation and baseplate flexibility. Linear and nonlinear spectral analyses show that increasing base flexibility generally increases frame lateral displacement and top moment of the column. Furthermore, moments at the top of the columns and the nonlinear base rotation may also increase with increasing base flexibility, especially for shorter period structures. Since many commonly used baseplate connections may be categorized as being semirigid, it is essential to design and model structures using realistic base rotational stiffness rather than simply use a fixed base assumption. The overall results also illustrate the range of increased seismic demand as a function of normalized rotational stiffness and structural period for consideration in design.